Disruption of the Glutamate–Glutamine Cycle Involving Astrocytes in an Animal Model of Depression for Males and Females - Rappeneau, Virginie; Blaker, Amanda; Petro, Jeff R.; Yamamoto, Bryan K.; Shimamoto, Akiko (Frontiers in Behavioral Neuroscience, 2016)
Background: Women are twice as likely as men to develop major depression. The brain mechanisms underlying this sex disparity are not clear. Disruption of the glutamate–glutamine cycle has been implicated in psychiatric disturbances. This study identifies sex-based impairments in the glutamate–glutamine cycle involving astrocytes using an animal model of depression. Methods: Male and female adult Long-Evans rats were exposed to chronic social defeat stress (CSDS) for 21 days, using a modified resident-intruder paradigm. Territorial aggression was used for males and maternal aggression was used for females to induce depressive-like deficits for intruders. The depressive-like phenotype was assessed with intake for saccharin solution, weight gain, estrous cycle, and corticosterone (CORT). Behaviors displayed by the intruders during daily encounters with residents were characterized. Rats with daily handling were used as controls for each sex. Ten days after the last encounter, both the intruders and controls were subjected to a no-net-flux in vivo microdialysis to assess glutamate accumulation and extracellular glutamine in the nucleus accumbens (NAc). The contralateral hemispheres were used for determining changes in astrocytic markers, including glial fibrillary acidic protein (GFAP) and glutamate transporter-1 (GLT-1). Results: Both male and female intruders reduced saccharin intake over the course of CSDS, compared to their pre-stress period and to their respective controls. Male intruders exhibited submissive/defensive behaviors to territorial aggression by receiving sideways threats and bites. These males showed reductions in striatal GLT-1 and spontaneous glutamine in the NAc, compared to controls. Female intruders exhibited isolated behaviors to maternal aggression, including immobility, rearing, and selfgrooming. Their non-reproductive days were extended. Also, they showed reductions in prefrontal and accumbal GFAP+ cells and prefrontal GLT-1, compared to controls. When 10 μM of glutamate was infused, these females showed a significant accumulation of glutamate compared to controls. Infusions of glutamate reduced extracellular glutamine for both male and female intruders compared to their respective controls. Conclusion: Twenty-one days of territorial or maternal aggression produced a depressive-like phenotype and impaired astrocytes in both male and female intruders. Disruption of the glutamate–glutamine cycle in the PFC-striatal network may be linked to depressive-like deficits more in females than in males.